Preparation of raw material for gelatin products - Hasdar, Muhamad (My University, 2024)
The preparation of raw materials for gelatin from the skin and bones will impact the quality of the gelatin produced. Skin and bones from abattoirs should be cleaned immediately of hair, meat residue, and fat. Skin and bone cleaning can be done manually but requires more time, effort, and cost. This can be done by acid or alkaline treatment while controlling the temperature between 4-5 ⁰C. This initial treatment can also break the fibrous protein bonds and peptide bonds in the skin before the thermal process carries out the hydrolysis process. Temperature control during pretreatment with low temperatures aims to reduce biological processes that can still occur, such as spoilage by microorganisms and ensure the quality of the protein that will be released during hydrolysis is not broken down into quaternary protein.